Succession process in rural family business in Brasil: a multicase study - Alcântara, Nádia de Barros (2014)
This paper deals with the succession process, within the context of brazilian rural enterprise development of family control. The main objective of this research is to deepen the understanding the succession process and the challenges faced during the development of rural enterprise. The method used is the multiple case study. The model proposed by Gersick et al. (1997) that considers the inter-relationships among the dimensions of family, management and ownership structure in a family business. It concludes that the motivations for the continuity of rural enterprise combine: a) the link between the family and the their business; b) the fact that the assets of the company consist in the capital reserve for the Family; c) a professional alternative for the family; and d) a business opportunity. Among the challenges identified, it is pointed out the implications of property for the adoption of growth strategies and the motivation to the younger generation to continue the family business. Also, it discusses the governance structures that emerge on the farm family business development. Noteworthy is the passage of an informal structure based on trust for more formalized governance structures, as meeting members and boards of directors.